As super-heroínas no cinema: a tipificação das personagens femininas em filmes da década de 2010 - Morais, Marina Vlacic (2021)
At a time when gender differences and struggles for equality and respect for women return to the agenda with great intensity in the various segments of society and in the media, it is necessary to understand the social context that involves the dissemination of information and the construction of images and speeches on the topic. Studying popular box office films such as superhero films is also to understand the context of where they come from, where they are aired and how they are consumed. The understanding of films produced within the commercial logic and their repercussions in the most varied media and social networks can help us to understand the contemporary female image. Given the above, the guiding question of this research is “What is the typification of the super heroines protagonists represented in the films of the decade of 2010?” and its main objective is to analyze the representation of super heroines in the selected films in order to identify the standard characters. As specific objectives it proposes: to verify how the characters are constructed in the film narrative (behavior, interactions, clothing, body); identify whether the characters break or maintain gender stereotypes; to relate female protagonism in the film genre with the cultural context experienced; and, map the typifications of super heroines in cinema. This research is based on the perspective of cultural studies and feminist theories of cinema. The main authors use Stuart Hall (1997, 2016), Raymond Williams (1979, 1993, 2003, 2007), Kathryn Woodward (2014) to talk about representation, identity, stereotypes and typification; Ana Carolina Escosteguy (2010, 2016), Guacira Lopes Louro (1997), Joan Scott (1988, 1992, 1995) and Heleith Safiotti (1987, 1994, 2004) exploring gender issues and feminist struggles / achievements; Laura Mulvey (1975), Ann E. Kaplan (1983), Hillary Neroni (2005), Janet McCabe (2004) and Giselle Gubernikoff (2016, 2019) from the perspective of feminist film criticism. The methodology used is the cultural-mediatic analysis, developed by the Cultural Studies and Audiovisuals Research Group of the Communication Postgraduation Program at UFSM. According to the characteristics of “super heroes” characters, the film genre that has the same name and also due to their protagonism in screen the super heroes of the decade of 2010 were determined totalizing ten superheroines with presence. Ro realize the analysis, we selected the characters that have a solo film and a female director, adding two films: Captain Marvel (2019) and Wonder Woman (2017). The analysis was carried out through the encounter between the representation of the characters and the cultural context experienced. The research determined the typification of the Captain Marvel character through the insertion of the “woman in an abusive relationship” and her trajectory of rupture and rediscovery of identity. Wonder Woman was typified as “woman in conflict with femininity,” because the character needs to affirm her identity against the patriarchal ideology that presents several barriers for the super heroine, in addition to trying at different times to fit her into the established social norms by the culture represented. Both characters present emerging perspectives on the complexity and diversity of the female gender identity, especially the character Captain Marvel.